Usefulness of foot-to-foot bioimpedance analysis for assessing volume status in chronic hemodialysis patients at the Aristide Le Dantec University Hospital (Senegal) - Keita, Niakhaleen; Faye, Maria; Seck, Sidy Mouhamed; Ndong, Boucar; Faye, Moustapha; Lemrabott, Ahmed Tall; Ba, Bacary; Ba, Mamadou Aw; Sy, Abdou; Ndongo, Modou; Ndiaye, Babacar; Ka, Elhadji Fary; et al. (Journal of Clinical Nephrology, 2021)
Introduction: Determination of dry weight is one of the daily goals to achieve in hemodialysis. The aim of this study was to validate the use of bioelectrical impedance analysis (BIA) in estimation of dry weight in a population of Senegalese chronic hemodialysis patients. Patients and methods: A 9-week cross-sectional study was carried out at the hemodialysis unit of Aristide Le Dantec University Hospital. Adult patients with no previous hospital history were included. The total body water (TBW) was measured with a single frequency bioelectric impedance foot-to-foot analyzer, before and after six successive hemodialysis sessions. These results were compared with those from clinical measurements with the Watson equation using a Student’s t-test and Bland-Altman analysis. Results: 264 measurements were made in 22 patients (46.6 years, 54.5% men, 92.3 months on dialysis, 62.7 kg mean dry weight). A significant reduction in weight (ΔWeight = 2.0 ± 1.1 kg; p < 0.0001) and in TBW measured by the BIA (ΔTBWBIA = 3.3 ± 1.0 liters; p < 0.0001)) or calculated by Watson’s equation (ΔTBWWatson = 0.5 ± 0.2 liter; p = 0.0001) was observed. There was a strong linear correlation and agreement between the 2 TBW measurements in pre-dialysis. In post-dialysis the concordance diagram indicated a bias = –2.2 and wide agreement limits. Conclusion: The BIA allows reproducible and reliable measurements and a fair estimate of the TBW in pre-dialysis.